Gastrointestinal bleeding of hidden origin Diagnostic value of jejunal endoscopy - Aizen Tub, Bernardo; Beltrán Guañarita, Jorge; Gutiérrez Galiana, Horacio; Gómez Fossati, Carlos (Cirugía del Uruguay, 1991)
The authors present a case of digestive bleeding of obscure origin due to vascular malformation of the upper jejunum. They make considerations on the entity and describe pre and intraoperative diagnostic methods and come to the conclusion that pre and intraoperative endoscopy is the procedure of election in their management.